2016
DOI: 10.1111/ens.12212
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding supports reclassification of JapaneseChironomusspecies (Diptera: Chironomidae)

Abstract: Non‐biting midges (Diptera: Chironomidae) adapt to species‐specific environmental conditions and hence are promising bioindicators for aquatic and ecotoxicological monitoring. Although their utility for these purposes was historically limited by difficulties in their morphological identification, DNA barcoding offers a possible solution. Here, eight Japanese species of the genus Chironomus, which is characterized by its worldwide distribution and abundance among Chironomidae, were subjected to DNA barcoding us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 62 publications
(153 reference statements)
4
20
0
Order By: Relevance
“…Chaudhuri et al 1992;Amora et al 2015, Martin 2017, and molecular analysis, with some limited cytological studies (Nath and Lakhotia 1989, and Gupta and Kumar 1991, Martin 2017. Those used for molecular analysis are listed in Pramual et al (2016) and confirmed the conclusion from morphological and cytological studies, that C. kiiensis (group B of Kondo et al 2016) was a junior synonym of C. striatipennis. Kondo et al (2016) considered only the Barcode sequences and concluded from these that they were identical or close relatives.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…Chaudhuri et al 1992;Amora et al 2015, Martin 2017, and molecular analysis, with some limited cytological studies (Nath and Lakhotia 1989, and Gupta and Kumar 1991, Martin 2017. Those used for molecular analysis are listed in Pramual et al (2016) and confirmed the conclusion from morphological and cytological studies, that C. kiiensis (group B of Kondo et al 2016) was a junior synonym of C. striatipennis. Kondo et al (2016) considered only the Barcode sequences and concluded from these that they were identical or close relatives.…”
Section: Methodssupporting
confidence: 69%
“…Those used for molecular analysis are listed in Pramual et al (2016) and confirmed the conclusion from morphological and cytological studies, that C. kiiensis (group B of Kondo et al 2016) was a junior synonym of C. striatipennis. Kondo et al (2016) considered only the Barcode sequences and concluded from these that they were identical or close relatives. Adults had been made available to Amora et al (2015) for their studies, so were not available for further study.…”
Section: Methodssupporting
confidence: 69%
“…Professional taxonomists are becoming rare even among biologists (Hopkins & Freckleton, 2002) and rapid and efficient tools might support the evaluation of biodiversity, especially those that are DNA‐based. Recent studies showed that DNA barcoding using a short sequence (ca 658 bp) of the mitochondrial COI in particular (Kondo et al., 2016; Kranzfelder et al., 2017; Pfenninger et al., 2007; Pramual et al., 2016) enables a fast and reliable taxon identification to species‐level of whole or even parts of specimens across any life stage (Hebert et al., 2003; Rach et al., 2017). Thus, it offers great promise in advancing freshwater bioassessment and monitoring routines (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic divergence is generally measured by the estimated pairwise distance between sequences, such as the p-distance, or more commonly, the distance calculated by the Kimura's 2-parameter (K2P) model (Kimura, 1980;Kondo, Ueno, Ohbayashi, Golygina, & Takamura, 2016). In this study, genetic distance was calculated with MEGA 5.0 (Tamura et al, 2011) with the default parameters and 1,000 bootstrap replicates under K2P model.…”
Section: Phylogenetic Analyses and Genetic Distancementioning
confidence: 99%